2019
DOI: 10.5761/atcs.oa.18-00113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Blood and Crystalloid Cardioplegia on Cellular Injury and Oxidative Stress in Cardiovascular Surgery

Abstract: Cardioplegia type creates similar effects on glycocalyx integrity. However, myocardial protection could be provided with warm blood cardioplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Ulugol et al [20] in a small sample of CABG patients receiving warm blood or cold crystalloid cardioplegia focused their attention on the postoperative cellular injury, and they concluded that both cardioplegic solutions created similar effects on glycocalyx integrity, but myocardial protection was better achieved with the use of warm blood cardioplegia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulugol et al [20] in a small sample of CABG patients receiving warm blood or cold crystalloid cardioplegia focused their attention on the postoperative cellular injury, and they concluded that both cardioplegic solutions created similar effects on glycocalyx integrity, but myocardial protection was better achieved with the use of warm blood cardioplegia.…”
Section: Discussionmentioning
confidence: 99%
“…From a technical-surgical point of view, the use of crystalloid cardioplegia may offer some advantage by allowing a longer time available for the packaging of distal coronary artery anastomoses and an operating bloodless field at the site of the anastomosis. However, if the surgeons prefer the warm cardioplegia, they should pay more attention to the interval time of administration, a shorter time of repetition of the dose being required to achieve effective myocardial protection [1,18,20,[28][29][30]. In fact, several studies performed on the use of warm blood cardioplegia have suggested the importance of the re-dosing interval [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these markers, near‐infrared spectroscopy (NIRS) gives noninvasive information on tissue perfusion. Sialic acid (SA) is a glycocalyx fragment which is shown through the effect of oxidative mediators, and its plasma levels increase after surgery 6 . Malondialdehyde (MDA) is one of the final products of polyunsaturated fatty acid peroxidation in the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hypervolemia and hemodilution causes increased plasma fHb levels, endothelial glycocalyx (EGL) damage, and activation of inflammatory processes. [ 3 4 5 ] There are in vitro and animal model data that find increased plasma free hemoglobin (fHb) related to inflammation, infection, platelet activation, vasculopathy and thrombosis. [ 6 ] In cardiac surgery, fHb is elevated due to both hemolysis caused by extracorporeal circuits,[ 4 ] and the inflammatory response induced by oxidative stress disrupting erythrocyte membrane integrity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] In cardiac surgery, fHb is elevated due to both hemolysis caused by extracorporeal circuits,[ 4 ] and the inflammatory response induced by oxidative stress disrupting erythrocyte membrane integrity. [ 5 ] It has been shown in studies that fHb causes end organ damage and increases mortality, these data suggest that an increase in fHb may be a biomarker for poor clinical outcomes. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%